Iowa and Eugene, Oregon, Orthopaedics - Buckwalter, Joseph A (Dept. of Orthopaedics, The University of Iowa, 2003)
Over the last 50 years, the commitment of orthopaedic surgeons to basic and clinical research and evaluation of treatment outcomes has made possible remarkable improvements in the care of people with injuries and diseases of the limbs and spine. A group of Oregon orthopaedic surgeons has had an important role in these advances, especially in the orthopaedic specialties of sports medicine and hip reconstruction. Since Don Slocum (Iowa Orthopaedic Resident, 1934-1937), started practice in Eugene, Oregon, in 1939, three orthopaedic surgeons, Denny Collis, Craig Mohler and Paul Watson, who received their orthopaedic residency education at the University of Iowa, and three orthopaedic surgeons, Stan James, Tom Wuest and Dan Fitzpatrick, who received their undergraduate, medical school and orthopaedic residency education at the University of Iowa, have joined the group Dr. Slocum founded. These individuals, and their partners, established and have maintained a successful growing practice that serves the people of the Willamette valley, but in addition, they have made important contributions to the advancement of orthopaedics.